Biodiesel production from waste cooking oil using copper doped zinc oxide nanocatalyst – process optimisation and economic analysis. (7th May 2020) - Sandhya, R.; Velavan, R.; Ravichandran, J.
India is the world's third largest consumer of energy. India's energy consumption consists of 44% coal, biomass and waste 24%, petroleum and other liquids 23% and other renewable sources such as wind, solar, nuclear and biofuels. Due to the shortage of diesel and increasing prices, biodiesel gained its importance as an alternate to the petroleum based fuels. This paper deals with the transesterification of waste cooking oil to biodiesel with copper doped zinc oxide nanocatalyst under varying parameters such as oil to methanol ratio (1:2-1:5 mol), catalyst loading (2-8% w/w), reaction time (30-60 minutes) and temperature (40-70°C). Results show that the maximum yield of about 97.7% was obtained at optimum reaction conditions. This result is further validated. The economic analysis of biodiesel production is carried out and the cost of biodiesel per litre works out to be 68 rupees INR ($0.99). [Received: August 3, 2018; Accepted: June 1, 2019]